2022
DOI: 10.1007/s11356-022-23951-4
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of chitosan/erythritol/graphene oxide composites for simultaneous removal of some toxic species from simulated solution

Abstract: In this study, chitosan (Ch) is adapted via green methodology including sonication induced crosslinking with different weight ratios of erythritol (Er) from (Ch-Er)1 to (Ch-Er)4. The products were casted in the form of thin films. The chemical modification was proved via FTIR spectroscopy. Then, the modified products were verified via an atomic force microscopy (AFM) investigation for their topography and surface properties. The data revealed that the optimized sample was (Ch-Er)3. This sample was further modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…This indicates that the adsorption was better fit by pseudo-first order and implies that the adsorption process is probably due to formation of chelate structure or electrostatic attraction between the active groups on the chitosan derivative and the metal ions. This finding is in a good agreement with our previous work [23,89,90]. The intraparticle diffusion model for the adsorption of both Pb(II) and Cr (VI) by CsAA 3 Cl revealed three regions: 1st step hydrogel diffusion, which corresponds to the rapid adsorption of metal ions from the aqueous phase to the boundary layer of the hydrogel; 2nd step gradual adsorptions, which correspond to the diffusion of metal ions within the porous sites of the hydrogel; and 3rd step equilibrium stage, which is the adsorption of metal ions into the interior surface of the hydrogel.…”
Section: Adsorption Kineticssupporting
confidence: 94%
See 1 more Smart Citation
“…This indicates that the adsorption was better fit by pseudo-first order and implies that the adsorption process is probably due to formation of chelate structure or electrostatic attraction between the active groups on the chitosan derivative and the metal ions. This finding is in a good agreement with our previous work [23,89,90]. The intraparticle diffusion model for the adsorption of both Pb(II) and Cr (VI) by CsAA 3 Cl revealed three regions: 1st step hydrogel diffusion, which corresponds to the rapid adsorption of metal ions from the aqueous phase to the boundary layer of the hydrogel; 2nd step gradual adsorptions, which correspond to the diffusion of metal ions within the porous sites of the hydrogel; and 3rd step equilibrium stage, which is the adsorption of metal ions into the interior surface of the hydrogel.…”
Section: Adsorption Kineticssupporting
confidence: 94%
“…Therefore, several isotherm models were proposed to denote the mechanism of the process. In the present work, two-parameter (Freundlich and Langmuir) and three-parameter (Redlich-Peterson) adsorption isotherm models were applied as they are the most common models tested by several authors [89][90][91]. All models were fit utilizing the non-linear fitting method by Origin Pro.…”
Section: Adsorption Isotherm Modelsmentioning
confidence: 99%
“…The intensity of this layer increased with increasing removal capacity. In our previous works, 34,35 we could apply the AFM for confirming the adsorption process by comparing the AFM outcomes before and after metal uptake. We found that the adsorbed species appear as a bright layer covering the surface causing the increase in the height measurement and the change in roughness values.…”
Section: Adsorption Kinetics 381 Adsorption Kinetics Of the Chitosan-...mentioning
confidence: 99%
“…Hg 2+ and MB dye have attained the maximum removal performance of 277.4 and 57.992 mg/g, respectively. In another work, 35 CH/erythritol/GO products were prepared by green protocols as sorbents for some toxic pollutants from simulated solutions. The synthesis plan was guided by the atomic force microscopy (AFM) outcomes to select the optimum sorbent at each step.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels have been widely used in different applications such as agriculture, [1] tissue engineering, [2] wound dressing, [3] biosensors, [4] and sorbents for removal of dyes [5] and heavy metals [6] . Currently, hydrogels based on natural polymers are replacing the petroleum‐based ones in different applications to protect the environment and to achieve sustainability [7] .…”
Section: Introductionmentioning
confidence: 99%